2006
DOI: 10.1088/0022-3727/39/22/004
|View full text |Cite
|
Sign up to set email alerts
|

Structure and photoluminescence properties of Fe-doped ZnO thin films

Abstract: Zn1−xFexO films were prepared by the radio-frequency (rf) magnetron sputtering technique on n-Si substrates with a composite target of a ceramic polycrystalline ZnO containing several Fe pieces on the surface. X-ray photoelectron spectroscopy study of the Zn1−xFexO films shows that Fe in the as-deposited film exists mainly in the form of Fe2+. And x-ray diffraction spectra show that all the films exhibited c-axis orientation. The room temperature photoluminescence (PL) properties of the Zn1−xFexO films were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(47 citation statements)
references
References 19 publications
4
43
0
Order By: Relevance
“…The 2θ corresponding to the (002) reflection shifts to a lower value with Al-Fe co-doping in ZnO indicating expansion of the unit cell along the c-axis. 16 The observed increase in FWHM and decrease in intensity with Al-Fe co-doping indicates some detoriation in the crystallinity of the ZnO thin film. 17 The PL spectrum of ZAF thin film shows a broad spectrum in the range 1.8 eV to 3.75 eV (figure 4).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The 2θ corresponding to the (002) reflection shifts to a lower value with Al-Fe co-doping in ZnO indicating expansion of the unit cell along the c-axis. 16 The observed increase in FWHM and decrease in intensity with Al-Fe co-doping indicates some detoriation in the crystallinity of the ZnO thin film. 17 The PL spectrum of ZAF thin film shows a broad spectrum in the range 1.8 eV to 3.75 eV (figure 4).…”
mentioning
confidence: 93%
“…The spectrum is fitted to Gaussian curve and is a combination of five peaks centred at 3.18 eV, 2.7 eV, 2.59 eV, 2.35 eV and 1.99 eV. Apart form the UV emission (3.18 eV) corresponding to near band edge, 16,18 visible emission in the blue region (2.7 eV), blue-green region (2.59 eV and 2.35 eV) and orange region (1.99 eV) are observed. The emissions in the visible region indicate the presence of high defect concentration in ZAF film.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sŰp and pŰd exchange interactions between ZnO as host and Fe as dopant give rise to a negative and positive correction to the conductionand valence-band edges, leading to narrowing of the band gap. Thus, the red-shift and quenching of the UV emission peak in the doped sample provide further evidence of the fact that Fe substitutes for Zn in the ZnO crystal [41]. The broad defect-related emission peak was deconvoluted into Gaussian peaks at 474 nm, 489 nm, 499 nm, 551 nm, and 563 nm.…”
Section: Optical Characterization Of Zn 1−x Fe X O Nanotubesmentioning
confidence: 79%
“…The blue emission at 376nm is attributed to the defect-related emission, particularly interstitial zinc defects [18]. For the ZnFe2O4 nanocomposite samples, a second emission band in the yellow-orange region centred at about 647nm is observed, which is significantly contributed to by the Fe-Zn phase [19]. It can be observed that the sample gives out orange-yellow light, which corresponds to the FL spectrum result [16].…”
Section: Absorption Spectroscopymentioning
confidence: 87%